2014
DOI: 10.1063/1.4902869
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear bionic acoustic metamaterials

Abstract: Articles you may be interested inAn acoustic lens built with a low dispersion metamaterial J. Appl. Phys. 117, 034904 (2015); 10.1063/1.4905295 Achieving selective interrogation and sub-wavelength resolution in thin plates with embedded metamaterial acoustic lenses Effective medium theory of thin-plate acoustic metamaterials J. Acoust. Soc. Am. 135, 1844 (2014); 10.1121/1.4868400Broadband field rotator based on acoustic metamaterials Appl. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The result suggested that the vibration modes of the rubber membrane with 0.1 mm thickness be very intensive, with only about 0.1 Hz interval and mainly the Z-direction vibration mode, which also corresponds to the results of Figure 5. Since the rigidity of membrane in the literature was small, the membrane modes are dense under the low vibration frequency, and such a property can reach to the extreme in mammalian cochlea [19]. With the film thickness increasing to 0.5 mm, although the vibration modes stay intense, the average interval is larger than 10 Hz.…”
Section: -P5mentioning
confidence: 98%
See 1 more Smart Citation
“…The result suggested that the vibration modes of the rubber membrane with 0.1 mm thickness be very intensive, with only about 0.1 Hz interval and mainly the Z-direction vibration mode, which also corresponds to the results of Figure 5. Since the rigidity of membrane in the literature was small, the membrane modes are dense under the low vibration frequency, and such a property can reach to the extreme in mammalian cochlea [19]. With the film thickness increasing to 0.5 mm, although the vibration modes stay intense, the average interval is larger than 10 Hz.…”
Section: -P5mentioning
confidence: 98%
“…However, it is difficult to put the structures with excellent vibration reduction ability in the thickness direction into the applications of the vibration and noise reduction for aircrafts and automobiles due to the oversize mass. Numerous researches have been conducted for a e-mail: ejhwu@mail.xjtu.edu.cn the important applications of the acoustic metamaterials in low-frequency noise and vibration reduction [17][18][19][20][21]. Particularly, a membrane-type acoustic metamaterials with a dynamic negative mass had been proposed in 2008 [22], and the oblique incidence acoustic absorptivity, especially in the range of 100-1000 Hz, was tested by the standing impedance tube method, which provided a new solution for engineering vibration and noise reduction [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of acoustic metamaterials is that they produce a deep subwavelength effect in acoustic devices, which is favorable to develop small-scale AEH devices for low frequencies. For instance, Yuan et al [60] proposed a helix-type AEH structure that represents one type of bionic acoustic metamaterials [61]. The helix structure changes the sound propagation path and achieves low-frequency AEH in a compact design.…”
Section: Established Aeh Approachesmentioning
confidence: 99%
“…The finite element method (FEM) is the most commonly used approach to biomechanical modeling and several studies on fluid-structure interaction can be found in literature. [25][26][27][28][29] However, no significant example of application of FE to the determination of HRTF is available in literature. Finite element (FE) models may solve this problem but no significant example of their application is documented in literature.…”
Section: Introductionmentioning
confidence: 99%